The perils of legally defining disinformation - Ronan Ó Fathaigh; Natali Helberger; Naomi Appelman (Internet Policy Review, 2021)
EU policy considers disinformation to be harmful content, rather than illegal content. However, EU member states have recently been making disinformation illegal. This article discusses the definitions that form the basis of EU disinformation policy, and analyses national legislation in EU member states applicable to the definitions of disinformation, in light of freedom of expression and the proposed Digital Services Act. The article discusses the perils of defining disinformation in EU legislation, and including provisions on online platforms being required to remove illegal content, which may end up being applicable to overbroad national laws criminalising false news and false information.
Keywords: 300; Disinformation; EU law; EU legislation; Freedom of expression; Platforms